Reform of Guardianship in Islamic Family Law in Tunisia, Egypt, and Indonesia - Muhammad Iqbal; Rahmad Wildan; Ahmad Alfarisi (USRATY : Journal of Islamic Family Law, 2025)
The reform of guardianship has become a focal issue in Islamic family law, particularly regarding the balance between religious authority and gender equality. This study aims to analyze the transformation of guardianship law in Tunisia, Egypt, and Indonesia through a comparative perspective grounded in contemporary Islamic jurisprudence. Employing a qualitative approach, this research explores legal documents, statutory frameworks, and scholarly discourses to examine how each country reinterprets the concept of guardianship within its sociopolitical and religious context. The findings reveal that Tunisia, influenced by progressive legal reform, has eliminated the obligatory role of the male guardian in marriage, redefining guardianship as a partnership based on mutual consent. Egypt retains the classical fiqh framework but applies flexible judicial interpretations to safeguard women’s autonomy within the boundaries of Sharia. Indonesia adopts a balanced approach by preserving the guardian’s authority under religious principles while harmonizing it with state regulation through the Compilation of Islamic Law. The study concludes that these variations reflect different paths of Islamic legal adaptation driven by modernity, political transformation, and gender discourse. This research contributes to the development of Islamic legal thought by demonstrating how contemporary jurisprudence can respond critically to evolving demands for equality and justice in Muslim family law.